In Vitro Infrared Thermographic Assessment of Temperature Change in the Pulp Chamber during Provisionalization: Effect of Remaining Dentin Thickness. (10th November 2020) - Lipski, Mariusz; Woźniak, Krzysztof; Szyszka-Sommerfeld, Liliana; Borawski, Mariusz; Droździk, Agnieszka; Nowicka, Alicja
Abstract : Interim crowns and partial fixed dental prosthesis materials generate exothermic heat during polymerization. The amount of heat transmitted to the pulp chamber can be a function of several factors, including the thickness and quality of the remaining dentin after crown preparation. The aim of this in vitro study was to measure with infrared thermography the temperature changes on the adjacent surface of the chamber roof of premolar teeth extracted from young and old patients (having different thicknesses of remaining dentin after crown preparation) during fabrication of provisional resinous restorations. Twenty extracted human first and second maxillary premolar teeth (10 from young patients, with a relatively large pulp chamber, and 10 from older patients, with a relatively small pulp chamber) were used. The roots were sectioned to expose the inner side of the chamber roof, and the crowns were provisionalized after preparation for a metal-ceramic crown. Two provisional materials, Turbo Temp 2 and Luxatemp Fluorescence, were used. Temperature changes on the inner side of the chamber roof were measured at 2-second intervals using an infrared thermal imaging camera. After completion of the temperature recordings, the teeth were sectioned and the remaining dentin thickness was determined. The older group (mean thickness: 2.82 mm) and younger group (mean thickness: 1.9 mm) differed significantly in dentin thickness (P < 0.014 ). The mean greatest temperature increases recorded on the chamber roof of teeth with less remaining dentin were 4.07°C for Turbo Temp 2 and 3.94°C for Luxatemp Fluorescence, while increases in the premolars with greater dentin thickness were 1.69°C for Turbo Temp 2 and 1.64°C for Luxatemp Fluorescence. Significant interactions were found between tooth groups (P < 0.000001 for Turbo Temp 2 and for Luxatemp Fluorescence). No significant differences were found between assessed materials regardless of the thickness of the remaining dentin (P > 0.38 for the older group and P > 0.29 for the younger group). Dentin had a significant effect in limiting the temperature increase generated during polymerization of provisional materials, indicating good thermal insulating properties of this tissue. A remaining dentin thickness of 1.9 mm or more is sufficient to protect the pulp from any temperature increase during provisionalization using tested materials.